The use of unaided augmentative and alternative communication strategies to support learners in South Africa special schools : a study of teachers' perceptions. - Bornman, Juan, 1968- (University of Pretoria, 2020)
Mini Dissertation (MAAC)--University of Pretoria, 2019.